Multicenter Evaluation of Commercially Available Methods for the Immunological Determination of Plasminogen Activator Inhibitor-1 (PAI-1) - Declerck, P J; Moreau, H; Jespersen, J; Gram, J; Kluft, C (Thrombosis and Haemostasis, 1993)
In order to evaluate the comparability of data obtained with various available kits for the immunological determination of PAI-1 antigen in plasma and in order to investigate the underlying cause of observed differences, e. g. problems of specificity or of proper calibration of the provided standard, a multicenter study was organised in the framework of the Subcommittee of Fibrinolysis of the Scientific and Standardization Committee.Eight different plasma samples were distributed among 16 laboratories: a pooled normal plasma, NIBSC 87/512, PAI-1 antigen depleted plasma, PAI-1 depleted plasma supplemented with 59 ng/ml active PAI-1 and four different individual plasma samples. A considerable variation in absolute values is observed between the various kits, e.g. in pooled normal plasma a value is found ranging between 7.4 and 28 ng/ml. Harmonization of all data relative to the PAI-l-depleted plasma supplemented with an exact amount of active PAI-1 (59 ng/ml), followed by a statistical analysis using a two way analysis of variance, revealed that 6 out of 7 kits yielded values that were not significantly different with coefficients of variation around 30%. Correlations between the values obtained with these kits yielded slopes between 0.75 and 1.44 with correlation coefficients between 0.973 and 0.999. Values obtained with one kit appeared to be significantly different (even after harmonization) from the other kits (p <0.001 to p <0.05). Comparison of PAI-1 antigen with the PAI activity values in the analysed samples suggests that one kit may deal with a problem of a difference in reactivity between active and latent PAI-1.In conclusion 6 different kits yield results that, only after harmonization, are comparable and do correlate very well. Thus proper calibration of the provided standards may solve the majority of the problems observed with PAI-1 antigen kits. Differential specificity towards different conformational forms of PAI-1, as a consequence of the use of different monoclonal antibodies, is a minor, but a potential problem, that needs to be considered when comparing data obtained with various methods.